Evaluación de la incorporación de productores quinueros al Sistema Integrado de Pensiones - Ramiro Gamboa Rivera (Institute for Advanced Development Studies (INESAD), 2023)
– This paper describes the current functioning of the retirement system in Bolivia. In addition, I rise scenarios related to old age benefit considering the quinueros; which means projections to the pension amounts that they (quinoa producers) could obtain based on the frequency of contributions, quotation amounts and requirements. In order to have an adequate understanding of the issue, I begin with a brief history of the pension reform over tie in Bolivia, continuing with a description of the current system and then characterizing the current benefits (costs, payment modalities, benefits, beneficiaries, coverage, coverage, cases of death and disability etc., both for dependent and independent workers). Subsequently, I describe the instrumentation that the Government performs for quotes and amounts of pension. Finally, I present the modalities and characteristics of access to the solidarity of old age, and the scenarios of the nominal and real payment of the pension that a quinoa producer could obtain in case of joining the pension system.
Keywords: J01; J26; J83; 330; Labor Economics; retirement; worker's rights